Kodų kaita joniškiečių šnekamojoje kalboje - Urnėžiūtė, Rita (Kalbotyra, 1998)
The article deals with some problems of code-switching theory. It also focuses on the following issues: 1) the concept and definition of the phenomenon in Lithuanian linguistic literature. 2) the recent trends of code-switching researches (attention is focused on conversational code-switching analysis), 3) the possibility to use modern code-switching theories and methods of research investigating spoken Lithuanian (especially in urban multidialectal and multilingual communities, rural areas of dialect or language contact, also interrelations of dialects and the standard language). The author analyses some short conversations in order to reveal code-switching between two varieties of spoken Lithuanian: the dialect and urban spoken language.